REFLECTARRAY ANTENNAS FOR STRATEGIC DEFENCE TECHNOLOGY - Muhammad Yusof Ismail; Muhammad Inam Abbasi (2012)
This book is designed to present fundamental concepts and principles of reflectarray antenna design for strategic defense technology. The concepts of reflectarrayantenna are explained in details relating to its basics on microwave propagation and Maxwell’s equations. Basic defense technology is briefly explained for the applicability of reflectarray antennas in defense systems.methods of active reflectarray antennas with radar cross section optimization. Reflectarray Antennas for Strategic Defense Applications offers an excellent insight on printed reflectarray antennas from the theoretical to the practical considerations; hence it is recommended to be used for design engineers, postgraduate students and researchers in communications technology.